An armadillo-domain protein participates in a telomerase interaction network - Dokládal, Ladislav; Benková, Eva; Honys, David; Dupľáková, Nikoleta; Lee, Lan-Ying; Gelvin, Stanton B; Sýkorová, Eva (Plant molecular biology, 2018)
Arabidopsis and human ARM protein interact with telomerase. Deregulated mRNA levels of DNA repair and ribosomal protein genes in an Arabidopsis arm mutant suggest non-telomeric ARM function. The human homolog ARMC6 interacts with hTRF2. Telomerase maintains telomeres and has proposed non-telomeric functions. We previously identified interaction of the C-terminal domain of Arabidopsis telomerase reverse transcriptase (AtTERT) with an armadillo/β-catenin-like repeat (ARM) containing protein. Here we explore protein-protein interactions of the ARM protein, AtTERT domains, POT1a, TRF-like family and SMH family proteins, and the chromatin remodeling protein CHR19 using bimolecular fluorescence complementation (BiFC), yeast two-hybrid (Y2H) analysis, and co-immunoprecipitation. The ARM protein interacts with both the N- and C-terminal domains of AtTERT in different cellular compartments. ARM interacts with CHR19 and TRF-like I family proteins that also bind AtTERT directly or through interaction with POT1a. The putative human ARM homolog co-precipitates telomerase activity and interacts with hTRF2 protein in vitro. Analysis of Arabidopsis arm mutants shows no obvious changes in telomere length or telomerase activity, suggesting that ARM is not essential for telomere maintenance. The observed interactions with telomerase and Myb-like domain proteins (TRF-like family I) may therefore reflect possible non-telomeric functions. Transcript levels of several DNA repair and ribosomal genes are affected in arm mutants, and ARM, likely in association with other proteins, suppressed expression of XRCC3 and RPSAA promoter constructs in luciferase reporter assays. In conclusion, ARM can participate in non-telomeric functions of telomerase, and can also perform its own telomerase-independent functions.
Keywords: proteiny huseníčku; telomerasa; Homologous recombination; Arabidopsis; holoenzymy; techniky dvojhybridového systému; reportérové geny; Arabidopsis Proteins; proteiny s doménou armadillo; Armadillo/β-catenin-like repeat; Telomerase activity; Two-Hybrid System Techniques; lidé; Telomerase; Humans; AtTERT; Protein–protein interaction; Armadillo Domain Proteins; Holoenzymes; Genes, Reporter; ARMC6